Automatic medicine distributor / Zaty Amanina Zailaludin, Muhammad Azizi Che Rashid and Muhammad Muzammel Ahmad - Zailaludin, Zaty Amanina; Che Rashid, Muhammad Azizi; Ahmad, Muhammad Muzammel (2015)
This project is aimed to develop an Automatic Medicine Distributor which aimed to remind patient at home to take medicine or supplement on time. Automatic Medicine Distributor is used at home to remind people especially some people tend to forget to on take their medicine and this will affect on their health. This project consists of a Servo motor that control by Arduino controller. The first circuit is used to control the number of pills or supplements by time and the second one is to control the motor. The Automatic Medicine Distributor is equipped with alarm system which is when the medicines or supplements are not taken from the small plate, the alarm will trigger until the medicines or supplements are taken. If the users don’t want to use the device, they can simply switch off the main switch. Therefore, this Automatic Medicine Distributor will help the people to take their medicine on time.